2012
DOI: 10.23986/afsci.6334
|View full text |Cite
|
Sign up to set email alerts
|

Protein crop production at the northern margin of farming: to boost or not to boost

Abstract: Global changes in food demand resulting from population growth and more meat-intensive diets require an increase in global protein crop production, not least as climate change and increasing scarcity of fresh water could restrict future production. In contrast to many other regions, in Finland climate change could open new opportunities through enabling more diverse cropping systems. It is justified to re-enquire whether the extent and intensity of protein crop production are optimized, resources are used effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 92 publications
0
28
1
1
Order By: Relevance
“…LMC International (2009a) reported that field pea and faba bean gross margin volatilities were lower or comparable to rapeseed, wheat or barley in four out of five case study regions (Table 1). Given the fact that in some regions, production risks are comparable with competing crops and that legumes and cereals respond differently to weather conditions; grain legumes can also play a role in spreading risk (Mishra and Lence 2005;Peltonen-Sainio and Niemi 2012).…”
Section: Volatility Of Grain Yields and Revenuesmentioning
confidence: 99%
“…LMC International (2009a) reported that field pea and faba bean gross margin volatilities were lower or comparable to rapeseed, wheat or barley in four out of five case study regions (Table 1). Given the fact that in some regions, production risks are comparable with competing crops and that legumes and cereals respond differently to weather conditions; grain legumes can also play a role in spreading risk (Mishra and Lence 2005;Peltonen-Sainio and Niemi 2012).…”
Section: Volatility Of Grain Yields and Revenuesmentioning
confidence: 99%
“…The corresponding numbers for the dairy region are 0.03, 0.18 and 0.15. The case regions thus represent substantial differences in frequencies of different cereal species and risks related to their production (Himanen et al 2012, Peltonen-Sainio andNiemi 2012). Regional datasets from Tike were used to record shifts in land use for different cereal species and cultivars.…”
Section: Methodsmentioning
confidence: 99%
“…At high latitudes, long days markedly enhance pre-anthesis development rate of cereals (Peltonen-Sainio and Rajala 2007), enabling timely harvest. Climatic constraints, however, cause substantial production uncertainty (Peltonen-Sainio et al 2009b, Peltonen-Sainio and Niemi 2012. In addition to the short growing season, northern conditions are characterized by harsh and variable winter conditions, a short period for successful spring sowing after snow melt and soil drying, early summer drought, and rapid changes at the end of summer towards non-growth-favoring autumn conditions (Mukula and Rantanen 1987, Peltonen-Sainio et al 2009a, 2011a, 2011b.…”
Section: Introductionmentioning
confidence: 99%
“…Another crop group receiving little breeding attention are grain legumes. Nordic feed protein has been replaced by imported and cheaper (genetically modified) soya bean (Stoddard et al 2009, Peltonen-Sainio andNiemi 2012). GM methods were discovered in the early 1970s (Cohen et al 1973, Berg et al 1974) but were not implemented in Europe as in the USA and South America (Jasanoff 2005).…”
Section: Agent and Structure Interactionsmentioning
confidence: 99%